2019
DOI: 10.1253/circj.cj-19-0007
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Fibrous Cap Structure of Coronary Lipid Plaque ― ST-Elevation Myocardial Infarction vs. Stable Angina ―

Abstract: overcome this bias. 5 So far, there have been no reports comparing the distribution and total sum area of non-culprit TCFA between acute coronary syndrome (ACS) and stable angina (SA) patients. The aim of the present study was therefore to compare non-culprit TCFA patterns using the novel volumetric analysis algorithm between patients presenting with ST-elevation myocardial infarction (STEMI) and SA. Methods Subjects were selected from the Massachusetts General Hospital (MGH) OCT Registry. The MGH OCT Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In this issue of the Journal, they showed that the lipid burden was greater and fibrous cap was thinner in the STEMI group than in the SA group. 3 This may be appropriate, as demonstrated by the many prior clinical studies showing similar results. 4,5 Interestingly, in the Bryniarski et al study, the baseline statin usage was significantly higher in the SA group, compared with the STEMI group, which may have affected the results.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…In this issue of the Journal, they showed that the lipid burden was greater and fibrous cap was thinner in the STEMI group than in the SA group. 3 This may be appropriate, as demonstrated by the many prior clinical studies showing similar results. 4,5 Interestingly, in the Bryniarski et al study, the baseline statin usage was significantly higher in the SA group, compared with the STEMI group, which may have affected the results.…”
mentioning
confidence: 89%
“…The current study by Bryniarski et al provides information on the 3-D evaluation of fibrous cap extent and TCFA distribution as a landmark of plaque vulnerability. 3 Future studies showing that this information leads to prediction of outcome and to prevention of cardiovascular events are expected.…”
mentioning
confidence: 99%
See 3 more Smart Citations